2021
DOI: 10.3390/ijerph18052656
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Therapeutic Horseback Riding Program on Social Interaction and Communication in Children with Autism

Abstract: Various therapeutic interventions have been studied and found to be effective in reducing the stereotypical behaviors of children with autism spectrum disorder (ASD). There has been increasing interest in using animal-assisted interventions (AAIs) as an alternative approach to therapeutic rehabilitation for children with ASD, and many studies have reported that AAI has significant benefits for the cognitive, psychological, and social behavior of children with ASD. The present study was designed to examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 23 publications
(10 reference statements)
0
34
0
9
Order By: Relevance
“…An update to the literature search produced three further studies, two of which provided results consistent with previous trials demonstrating improvements in socialization in children with ASD receiving equine-assisted services Zhao et al, 2021). These studies were, however, limited by similar issues identified in previous trials, such as a lack of blinding in outcome assessment.…”
Section: Summary Of Evidencementioning
confidence: 61%
See 1 more Smart Citation
“…An update to the literature search produced three further studies, two of which provided results consistent with previous trials demonstrating improvements in socialization in children with ASD receiving equine-assisted services Zhao et al, 2021). These studies were, however, limited by similar issues identified in previous trials, such as a lack of blinding in outcome assessment.…”
Section: Summary Of Evidencementioning
confidence: 61%
“…In an updated search from 2020 to 2021, two further studies evaluating equine-based approaches were identified. Zhao et al (2021) reported improvements in Social Skills Improvement System Rating Scales (SSIS-RS) assessed social skills in comparison to a routine activity control in 61 children receiving a 16 week protocol of THR. Peters et al (2021) evaluated an Occupational Therapy within an equine environment in comparison to a waitlist control involving Occupational Therapy in a garden environment.…”
Section: Resultsmentioning
confidence: 99%
“…Several previous AAI studies have found concurrent self-regulation and social outcomes in youth with ASD ( 45 , 46 ). There is increasing scientific interest in assessing self-regulation and social outcomes of THR in youth with ASD ( 47 , 48 ). However, to our knowledge the current paper is the first to report a mediation analysis, examining improved self-regulation as a mechanism for social outcomes within a randomized controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…Given the demonstrated importance of good psychomotor maintenance in achieving autonomy in ADL and quality of life, it is convenient to propose treatments that favor the development of these capacities, especially in people with neurodevelopmental disorders. AAI may be an adequate alternative to improve social interaction and communication skills since the animal acts as a social facilitator and a powerful motivator to carry out activities [15,53,54], directing this technique towards psychomotor and social objectives may be a quick and effective method for enhancing the autonomy of users with ASD and improving their quality of life.…”
Section: Discussionmentioning
confidence: 99%